Trust, hope, and collective action in fragile political settings: a qualitative comparative analysis of water user groups in Tunisia - Bhalla, S.; Garrick, D.; McDermott, C. L. (Elsevier, 2025)
Collective action theory acknowledges that self-governing institutional arrangements, such as water user groups, can successfully develop strategies to address natural resource problems. However, studies of collective action have largely neglected the role of social, political and/or ecological fragility, where institutional trust and hope may have been eroded over time, and where natural resources are severely depleted. This paper uses Qualitative Comparative Analysis (QCA) to examine the pathways that mediate the multi-faceted relationship between trust, hope, and collective action in the context of water user groups, addressing resource scarcity challenges in post-authoritarian Tunisia. The analyses are based on data from archival sources, key informant interviews, hydrogeological models, local inventories, and semi-structured interviews with members of 15 local water user groups in the Tunisian governorate of Kairouan. Results from Qualitative Comparative Analyses shed light on dynamics of trust and hope as well as the substitutability of shared norms under given ecological conditions. Results demonstrate that water users see social trust-based systems as an alternative to the coercive power of the state. Specifically we find that: (1) social cohesion and the expectation that other water users stick to local, often informal, rules were found to increase collective action, i.e. fee recovery, under systemic fragility; (2) resource scarcity, i.e. aquifer depletion, can serve as a driver of both conflict as well as cooperation, depending on conjoint social-ecological interactions; and, finally, (3) conflict is more frequently associated with low-hope environments, where users are unable to perceive the possibility of positive system change. These insights seek to inform more realistic policy reforms that are sensitive to a fragile water governance system prone to social unrest.